2017
DOI: 10.1371/journal.pone.0173751
|View full text |Cite
|
Sign up to set email alerts
|

Computer assisted electromagnetic navigation improves accuracy in computed tomography guided interventions: A prospective randomized clinical trial

Abstract: PurposeTo assess the accuracy and usability of an electromagnetic navigation system designed to assist Computed Tomography (CT) guided interventions.Materials and methods120 patients requiring a percutaneous CT intervention (drainage, biopsy, tumor ablation, infiltration, sympathicolysis) were included in this prospective randomized trial. Nineteen radiologists participated. Conventional procedures (CT group) were compared with procedures assisted by a navigation system prototype using an electromagnetic local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 19 publications
(26 reference statements)
4
33
1
2
Order By: Relevance
“…1.6 ± 1.3 mm. A randomized study on computer assisted electromagnetic navigation shows a median initial targeting accuracy of 4.1 mm for 60 needle placements . In this study too, further needle corrections where performed manually after the initial navigated needle placement.…”
Section: Discussionmentioning
confidence: 99%
“…1.6 ± 1.3 mm. A randomized study on computer assisted electromagnetic navigation shows a median initial targeting accuracy of 4.1 mm for 60 needle placements . In this study too, further needle corrections where performed manually after the initial navigated needle placement.…”
Section: Discussionmentioning
confidence: 99%
“…A phantom study [3] reported a median distance accuracy of 3.7 mm in out-ofplane trajectories using this navigation system. In addition, a prospective randomized clinical trial [10] demonstrated that the needle insertion accuracy was significantly improved with this navigation system, when compared to insertion with conventional CT guidance (median distance accuracy, 4.1 mm vs. 8.9 mm) in various clinical conditions including out-of-plane trajectory. Some robotic positioning systems have been commercialized, including iSYS (Kitzbuhel) [8,[11][12][13] and MAXIO (Perfint Healthcare) [14][15][16][17].…”
Section: Discussionmentioning
confidence: 96%
“…Other than our robot, several devices and robots to assist out-of-plane needle insertion have been evaluated. An electromagnetically guided system (IMACTIS) displays the needle path in real time on two-dimensional CT images reconstructed from preprocedural CT data [3,10]. A phantom study [3] reported a median distance accuracy of 3.7 mm in out-ofplane trajectories using this navigation system.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Xu et al [14] developed a smartphone augmented-reality application to provide visual guidance to the surgeon during the phase of angle selection of manual pre-insertion. With the Imactis TM commercial CTnavigation system, Durand et al [15] enhanced CT-guided interventions with a visual feedback of the trajectory of the needle before the insertion, thanks to electro-magnetic tracking. Another visual-guidance device for needle preinsertion assistance was proposed by Grasso et al [16].…”
Section: Related Workmentioning
confidence: 99%